Developing Balinese Local Culture Based English E-Media to Support the Implementation of Curriculum 2013 for the First Semester of Grade VII Junior High School - Ni Luh Putu Maya Apsari (Universitas Pendidikan Ganesha, 2017)
This design and development research aimed at designing and developing a culture-based English e-media to support the implementation of curriculum 2013 for the first semester of grade VII of junior high schools in Buleleng sub-district. This research focused on developing e-media that is integrated with Balinese culture. The object of this research was culture- based English e-media that was developed by using Adobe Flash CS6 program. The source of data was taken from the need analysis conducted by Dewi and Batan (2015), related literatures on developing the e-media, and the result of expert judgement. The data were analysed descriptively both qualitatively and quantitatively. This research was designed based on the adaptation of puffers et al.’s model (2007) that consisted of six phases namely: (1) identifying the problem, (2) describing the objective, (3) designing and developing the product, (4) testing the product by using expert judgement, (5) evaluating the testing result, and (6) communicating the testing result. The result of experts’ judgement score showed that the total mean score 3.8 which means the e-media had a good quality and it can be used in teaching and learning English for the first semester of grade VII of junior high schools in Buleleng.